Strength and Energy Evolution Law of Deep-Buried Granite Under Triaxial Conditions - Guo, Guangtao; Xu, Dingping; Feng, Guangliang; Wu, Xiaogang; Zhou, Yuxin (Frontiers in Environmental Science, 2022)
With the increasing global demand for clean and renewable energy, a large number of underground hydropower caverns are built-in deep mountain valleys in high-stress regions, the evolution of the mechanical properties of the surrounding rock of underground caverns under high-stress excavation requires urgent investigation. According to the deep-buried granite in the underground caverns of the Shuangjiangkou hydropower station, triaxial tests under confining pressures of 10 MPa, 30 MPa, 40 MPa, and 50 MPa were conducted by the MTS815 rock mechanics test system. Based on the stress-strain curve, the evolution law of the strength parameters of samples with the crack volume strain and energy with the energy consumption ratio under different confining pressures were analyzed. Our results showed that the stress-strain curve of the sample is divided into five stages with four points: the closing point, the crack initiation point, the damage point, and the peak point. The strength of each stage increases with the increase in the confining pressure. In addition, the failure of this granite is characterized by apparent shear failure. The internal friction angle and the cohesion increase rapidly with the increase in the crack volume strain, and they tend to be stable. Furthermore, the confining pressure profoundly influences the energy evolution law during the confining loading in the stable and unstable expansion stages of cracks, and the total energy, elastic strain energy, and dissipation energy at the stable and unstable expansion stages of cracks all increase with the increase in the confining pressure. Finally, the energy consumption ratio can represent the preliminary criterion of rock failure in terms of energy. With the increase in the confining pressure, the energy consumption ratio at the peak point gradually approaches 1.0, and the energy consumption ratio at the peak point, that is, the failure point of rock samples, steadily rises. These study results would be supplied to foresee natural catastrophes in constructing rock mass constructions.